PENGENAAN BEA KELUAR TERHADAP BARANG EKSPOR DAN EKSPOR BARANG YANG WAJIB MENGGUNAKAN LETTER OF CREDIT (L/C) - Sugianto Sugianto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
For all this time the export tax of spesificly things whose taking by the government is known as export, now became out tax , the exportir of nature sources commodity, of crude palm oil (CPO) commodity and mining product, bar of tin and for coffee commodity, cocou, and rubber is one of important commodity whose giving a lot of devisa as a payment to exportactivity and must using letter of credit L/C, for raise our country devisa